(untitled) (LACCEI, 2024)
This research analyzed the physical-mechanical behavior of the incorporation of gray cast iron chips to a mix design of 21 MPa, subjected to compression and flexural tests, corresponding to an age of 7, 14, 21 and 28 days and 7 and 28 days carried out under the parameters of the NTP, acquiring materials from the main quarries of Trujillo, under a strict quality control, with a selected population of 72 specimens with a pure experimental research design, with a quantitative methodology. The compression results show that the optimum result was reached in G4 = 10%, being 11.27% more resistant than the standard concrete and achieving a resistance of 252 Kg/cm2 (120.16%) in compression tests while in traction the most optimum result is G1 = 0% (standard concrete), reaching 39.60 Kg/cm2 (18.86%). It is established that the incorporation of gray cast iron chips favors a gain in resistance to compressive stresses, while in tensile stresses the behavior of the concrete is totally different in all the study groups.